The sexual self-concept and sexual satisfaction of single and coupled people - Antičević, Vesna (Array, 2017)
Aim. The aim was to investigate the moderating role of the attachment styles (in categories) of single and coupled people on the association between the cognitive-emotional aspects of sexuality and sexual satisfaction. Methods. The study included members of the general population of both sexes (No. of men=309, No. of women=323), of 20–65 years of age. Individual attachment styles were investigated using the Inventory of Experiences in Close Relationships (Kamenov and Jelić, 2003), while aspects of sexual self-concept (sexual self-esteem, sexual depression and sexual preoccupation) were studied using the Sexuality Scale (Snell and Papini, 1989). Sexual satisfaction was evaluated using the New Sexual Satisfaction Scale (Štulhofer and Buško, 2008). Results. When a person is in a relationship, sexual self-esteem and sexual depression are predictors of sexual satisfaction, regardless of the attachment style. The moderating role of the preoccupied and dismissive attachment styles was only determined for single persons: a) a preoccupied attachment style of a single persons increases the negative contribution of sexual depression to sexual satisfaction ; b) a dual role was determined for the preoccupied attachment style on sexual satisfaction: it is beneficial under conditions of low sexual self-esteem but detrimental under conditions of high sexual self-esteem, c) the dismissive style strengthens the association between sexual preoccupation and sexual satisfaction (sexual preoccupation increases sexual satisfaction, especially among single persons), d) the dismissive attachment style additionally reduces the sexual satisfaction of persons with low sexual self-esteem (especially if they are in a partner relationship).